2016
DOI: 10.3847/0004-637x/829/1/35
|View full text |Cite
|
Sign up to set email alerts
|

Transition Region and Chromospheric Signatures of Impulsive Heating Events. I. Observations

Abstract: We exploit the high spatial resolution and high cadence of the Interface Region Imaging Spectrograph (IRIS) to investigate the response of the transition region and chromosphere to energy deposition during a small flare. Simultaneous observations from the Reuven Ramaty High Energy Solar Spectroscopic Imager provide constraints on the energetic electrons precipitating into the flare footpoints, while observations of the X-Ray Telescope, Atmospheric Imaging Assembly, and Extreme Ultraviolet Imaging Spectrometer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 63 publications
5
56
0
Order By: Relevance
“…Tian et al (2015) also reported that the Si IV line is often not entirely redshifted but just shows an evident red-wing enhancement at the ribbons. It is worth mentioning that some fully redshifted Si IV profiles were reported by Warren et al (2016) and also reproduced in numerical simulations by Reep et al (2016). However, those Si IV profiles generally exhibit multiple components and might be better fitted by a double-or multiple-Gaussian function.…”
Section: Interpretation and Discussionmentioning
confidence: 65%
“…Tian et al (2015) also reported that the Si IV line is often not entirely redshifted but just shows an evident red-wing enhancement at the ribbons. It is worth mentioning that some fully redshifted Si IV profiles were reported by Warren et al (2016) and also reproduced in numerical simulations by Reep et al (2016). However, those Si IV profiles generally exhibit multiple components and might be better fitted by a double-or multiple-Gaussian function.…”
Section: Interpretation and Discussionmentioning
confidence: 65%
“…The presence of turbulent signatures over ~60 s means that the driver of turbulence persists for longer. Si IV emission in flares is usually well correlated with flare hard x-rays (HXRs) ( 19 ), which provide the most direct signature of intense energy deposition by flare-accelerated electrons in the lower atmosphere. In this flare, however, there is no detectable high-energy HXR emission, although the 6- to 12-keV x-rays rise rapidly as the Si IV intensity peaks, possibly indicating low-energy nonthermal electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al, 2015;Brosius, Daw, and Inglis, 2016;Graham and Cauzzi, 2015;Graham et al, 2020). The Si IV and C II spectra sometimes show persistent red-shifts or red-asymmetries of a few tens of km s −1 during the whole impulsive phase (Warren et al, 2016;Yu et al, 2020), which provide challenging constraints to the 1D loop models (e.g. Reep et al, 2016bReep et al, , 2018.…”
Section: Chromospheric Evaporation and Condensation With Irismentioning
confidence: 99%